2022
DOI: 10.3389/fnmol.2022.850849
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin-2 and Cerebral Stroke

Abstract: Stroke is a common and devastating disease with an escalating prevalence worldwide. The known secondary injuries after stroke include cell death, neuroinflammation, blood-brain barrier disruption, oxidative stress, iron dysregulation, and neurovascular unit dysfunction. Lipocalin-2 (LCN-2) is a neutrophil gelatinase-associated protein that influences diverse cellular processes during a stroke. The role of LCN-2 has been widely recognized in the peripheral system; however, recent findings have revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 119 publications
(174 reference statements)
0
7
0
Order By: Relevance
“…Lipocalin-2, which among its many functions can act as a inducer of chemokine expression [ 43 45 ], was identified as one of the DEG most highly responsive to RD, with a 42.9-fold increase at 1 dprd in the RNA-Seq analysis. We therefore chose to validate Lcn2 mRNA results and examine LCN2 protein expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipocalin-2, which among its many functions can act as a inducer of chemokine expression [ 43 45 ], was identified as one of the DEG most highly responsive to RD, with a 42.9-fold increase at 1 dprd in the RNA-Seq analysis. We therefore chose to validate Lcn2 mRNA results and examine LCN2 protein expression.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Lcn2, which has been implicated in induction of cytokine expression [ 43 45 ], was also very highly upregulated in the detached RPE. Greatly increased expression of Lcn2 mRNA in the detached RPE at 1 dprd was confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is not an MC medium condition-specific event, LCN2 expression was only induced upon IL-1β stimulation when the cells were in a spheroid state. Astrocyte-derived LCN2 is involved in chronic itch [ 37 ], cerebral stroke [ 38 , 39 ] and so on. To reveal the role of LCN2 in these diseases, IL-1β-dependent and TNF-α independent induction mechanism of the of HASTR/ci35 spheroids might be a useful tool.…”
Section: Resultsmentioning
confidence: 99%
“…Lcn2 is involved in multiple cellular processes, including cellular uptake of iron, apoptosis, suppression of invasiveness and metastasis, and glial activation. It also plays a crucial role in brain injury and recovery after ischemic and hemorrhagic stroke [ 30 , 31 ]. Another study has shown that Lcn2 may exert damaging effects after cerebral ischemia by inducing classical activation of astrocytes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%